Application of Technology in the Social Studies Learning Process at the Elementary School Level: Opportunities and Challenges - Wau, Maria Patrisia; Endu, Elisantinia; Lulu, Maria Julita; Odje, Maria Stefania; Itu, Maria Alexandra; Soro, Viorentina Meo; Ngadha, Christina; Tonda, Fransiskus (SAINTIS Publishing, 2025)
The purpose of this research is to explore opportunities and challenges by incorporating and implementing technology in the social studies learning process at the elementary school level. In this research process, the application of qualitative methods and case study approaches is used. One of the goals is to identify the benefits and barriers and the extent to which teachers and students are coping with them. Data sources are taken by conducting interviews, observations, and interviews with teachers, and relevant documentation. Afterwards, the authors conclude that technology allows greater access to learning resources, supports interactive learning and cooperative learning, young students have knowledge about experiments, and many others. However, there are also several challenges in its implementation. These challenges include infrastructure and access to technology tools, training and partnership development for teachers, and digitalization imbalances that exacerbate educational imbalances. This research highlights the importance of appropriate strategies and policies in overcoming these challenges and provides recommendations in optimizing elementary school social studies learning technology. Thus, this research is also expected to be able to provide understanding and become one of the references in developing learning by using technology, especially in social studies learning.